Seventh Five Year Plan 1985-90 A Summary - Planning Commission (Planning Commission, 1985)
Since the inception of planning process, the Indian economy has made steady progress towards the basic objectives of building an independent, self reliant economy, of establishing a social system based on equity and justice, to bring about a sharp reduction in social and economic inequalities inherited from the colonial era, and of laying a sound base for indigenous technological development. There is now fairly convincing evidence that specially since mid seventies, the Indian economy has moved to a higher growth path. The successful implementation of the Sixth Five Year Plan has been a major contributory factor to this welcome shift in the growth curve. The Seventh Plan builds on the strengths inherited from the past-the high rale of savings, the large pool of scientific, technical and managerial man-power, the resilience built against drought and international disturbances and the orientation of development efforts to benefit the poor. It is now possible to move faster towards the objective of self-sustaining growth with social justice.
Government of India Planning Commission